Technology of Production a New Type of Product in the Tourism Diversification - Kamolov Xudoyor Zoyirovich (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This article analyzes the scientific foundation of the development for a technology of production a new type of tourism and diversification tourism, explores the impact of diversification new tourism products in the tourism, as well as offers to create a new type of touristic routine, the introduction of special types of tour-packages and improve different kind od tourism types through the diversification of tourism products in Uzbekistan. Diversification of tourism products is one of the areas of continuous improvement of the activities of travel agencies and other organizations working in the field of tourism. A highly efficient travel agency strives to provide a variety of services to as many tourists as possible. This model of commercial success is typical of most tour firms in the modern tourism market. Success here depends on the quality and range of services offered (products, goods) and their volume. In connection with this approach, many travel companies try to diversify the type of services as much as possible to meet the needs of customers as much as possible. The practical significance of the work is the development of proposals to increase the efficiency of the travel agency. The goal is to increase the revenue of the travel agency by diversifying the services offered